Enhancing Growth Trajectories: The Role of Monthly Nutritional Support and Growth Dynamics in Preschool-aged Children (3-6 years) (Homoeopathy for All, 2026)
Preschool years, ranging from 3  to 6 years of age, mark a period  of rapid physical, cognitive, and  emotional development.1,2 Optimal  nutrition during this phase is vital  not only for maintaining adequate  health but also for ensuring proper  growth dynamics, which includes  height gain, weight gain, and brain  development.3 Monthly nutritional  support programs, especially in low resource settings, have emerged as  an essential intervention to bridge  dietary gaps, prevent malnutrition,  and promote holistic development in  children.4
Keywords: Paediatrics; Nutrition; Poshan; Anthropometric measures